2011
DOI: 10.1016/j.ophtha.2010.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Visual Outcome in Central Retinal Vein Occlusion

Abstract: Objective-To investigate systematically the natural history of visual outcome in central retinal vein occlusion (CRVO). Design-Cohort study.Participants-667 consecutive CRVO patients (697 eyes) with CRVO, first seen in our clinic from 1973 to 2000.Methods-At first visit, all patients had a detailed ophthalmic and medical history, and comprehensive ophthalmic evaluation. Visual evaluation was done by recording visual acuity, using the Snellen visual acuity chart, and visual fields with a Goldmann perimeter. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
209
3
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(226 citation statements)
references
References 34 publications
9
209
3
4
Order By: Relevance
“…However, Hayreh et al suggested that CVs formation may be associated with a delay in resolution of macular edema and worse prognosis. 9 Recent data from the SCORE study may indicate that the development of venous collaterals does not demonstrate an independent association with visual acuity in eyes with CRVO. 36 Although limited to only 15 instances of CV formation, our data did not demonstrate a significant difference in the incidence of collateral formation following CRVO in patients with or without DM.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, Hayreh et al suggested that CVs formation may be associated with a delay in resolution of macular edema and worse prognosis. 9 Recent data from the SCORE study may indicate that the development of venous collaterals does not demonstrate an independent association with visual acuity in eyes with CRVO. 36 Although limited to only 15 instances of CV formation, our data did not demonstrate a significant difference in the incidence of collateral formation following CRVO in patients with or without DM.…”
Section: Discussionmentioning
confidence: 95%
“…8 The ischemic CRVO generally presents with poorer visual acuity at baseline, worse visual prognosis and higher risk of developing neovascularization as compared with the nonischemic group. 8,9 Visual decline in patients with CRVO may occur from ischemic injury to the retina, macular edema, vitreous hemorrhage, retinal neovascularization, and/or neovascular glaucoma. 10 There is an associated vision-related decline in quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The ischemic subtype of CRVO accounts for about 20% of cases and is associated with worse initial presenting visual acuity (VA) and poor visual prognosis even after edema resolution. 6 A cohort study showed that presenting VA in ischemic CRVO patients was (6/30) or better in only 1% of ischemic CRVO patients compared with 78% of non-ischemic patients. 6 Furthermore, final VA after resolution was better than 6/30 in only 12% of ischemic CRVO patients compared with 83% in non-ischemic patients.…”
Section: Introductionmentioning
confidence: 99%
“…6 A cohort study showed that presenting VA in ischemic CRVO patients was (6/30) or better in only 1% of ischemic CRVO patients compared with 78% of non-ischemic patients. 6 Furthermore, final VA after resolution was better than 6/30 in only 12% of ischemic CRVO patients compared with 83% in non-ischemic patients. Stratifying patients early based on the perfusion state and the initial presenting visual acuity is useful in predicting outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation